RETRACTED: Thermal stability of water-in-oil microemulsions containing solubilized nutritional protein gelatin - Klimovitskaya Mariya; Skvortsova Polina; Zueva Olga; Zuev Yuriy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001